NILAI TAMBAH EKONOMIS PERKEBUNAN KARET RAKYAT KABUPATEN PELALAWAN DALAM PENDEKATAN NEW INSTITUTIONAL ECONOMIC - Romagia M.Si (VALUTA, 2016)
Pelalawan regency has the potential of smallholder rubber plantations are widespread. Extensive rubber plantations alone in 2014 reached 26415.90 ha or equal 7.20% of the totalplantation area overall. But until now the utilization of plantation products has not been ofgreat benefit both for the farmers and society in general. Therefore it is considered essential toincrease the economic value added of smallholder rubber plantations in Pelalawan. This studyuses a new institutional economic review. Results of the study found that approximately 76% ofhousehold income rubber farmers in the regency is supported by income from their rubberplantation. The study also found that so many layers of traders involved, making the chain themarketing of rubber in Pelalawan long enough and long chain trade system that resulted in alow selling prices at the farm level, hence farmers can only receive the price of rubbers. In theend, the study found that in order to increase economic value added of smallholder rubberplantations need to make institutional improvements rubber plantation in Pelalawan.